Caracterización morfológica floral de especies silvestres arbóreas (acnistus arborescens l. & erythrina edulis triana ex micheli) en el bosque siempre verde pie montano de la Cordillera occidental de Los Andes bspn01 de los 300 m.s.n.m. a 1400 m.n.s.m., provincia de Cotopaxi, 2018. - Herrera Amores, Diego Andrés (2018)
The present investigation was carried out in La Mana county in the Cotopaxi province, in the bioclimatic floor (BsPn01) of Pie Montano Evergreen Forest of the Western Cordillera of the Andes between 300 m.a.s.l. and 1400 m.a.s.l. with the purpose of characterizing the floral morphology of tree species Cojojo (Acnistus arboresnces L.) and porotillo (Erythrina edulis Triana ex Micheli). Two phases were used. On the first phase, the filed phase, the external characteristics of the flower were analyzed using the established methodology of collection, conservation and transport of flowers. In the laboratory phase, the internal characteristics of the flower were determined, which was based on the guide "The flower, inflorescence and fruit", was by Biologist. Richard Javier Huaranca Acostupa (2010). In the species under study, it was determined that the flowering stage of Acnistus arborescens L, begins in the second week of the month of February and concludes the third week of the month of April. And this presents an inflorescence of the simple umbel type, with heterooclamid. The calyx is gamosepalous with 5 sepals. The stamen consists of five anthers and the gynoecium has a superior, bicarpel, bilocular and poly-ovular. In the case of Erythrina edulis Triana ex Micheli, the flowering stage starts from the fourth week of February and ends the fourth week of April. With a cluster inflorescence, with heteroclamid flowers with a ligulate corolla, hermaphrodites. Gamosepalous calyx with three sepals. The stamen consists of four stamens with greater length and four stamens of shorter length and the gynoecium has a superior, unicarpel, unilocular and poly-ovular